Author Correction: Rice auxin influx carrier OsAUX1 facilitates root hair elongation in response to low external phosphate - Jitender Giri (Nature Portfolio, 2018)
The original version of this Article omitted the following from the Acknowledgements:‘We also thank DBT-CREST BT/HRD/03/01/2002.’This has been corrected in both the PDF and HTML versions of the Article.